Trusted Partnerships in the Faith Community Facilitate Awareness and Recruitment of African Americans for Alzheimer's Disease Studies. (20th December 2022) - Williams, Kelvin; Henderson, Shelby; Lloyd, Shawnta'; Caban‐Holt, Allison M; Starks, Takiyah D.; Martin, Patrick McPhail; Bozoki, Andrea C.; Price, Stephen Russ; Plassman, Brenda L; Welsh‐Bohmer, Kathleen A.; Byrd, Goldie S.
Abstract: Background: Historical mistrust in medical systems has resulted in low Alzheimer's disease (AD) research participation among African Americans (AA). However, the faith community remains a trusted institution among many AAs and can be a major facilitator for increasing AA AD awareness and research. To better understand the health needs of AAs and build relationships with faith organizations in the Triad area of North Carolina, we conducted a community needs assessment (CNA) among local faith leaders. Method: A mixed‐methods CNA was conducted. Quantitative data was collected from 44 pastors of AA churches via surveys that assessed resources, church demographics, and health topics of concern. Descriptive statistics were conducted for survey data. Qualitative data was collected during "listening tours" among pastors, with specific emphases on healthy aging, trust in medical systems, and research perceptions. Data from "listening tours" were analyzed using thematic analysis. Result: Our CNA indicated that AD was a common health topic of concern among pastors and their congregations. This is likely influenced by the composition of the churches, given that more than half of the pastors reported that at least 30% of their congregation was 65 years of age or older. During 2021, collaborations between MACHE and faith leaders produced 3 webinars, 13 food distributions, and 4 community outreach events. Over 40, 000 people were provided AD and brain health education; 1, 961 community members expressed interest in AD research opportunities; and 580 AAs enrolled in the NC Registry for Brain Health over an 8‐month period in 2021, during the COVID‐19 pandemic. Conclusion: Through a 3‐year partnership, the TPN and MACHE have significantly increased brain health awareness and AA participation in AD research through grassroots community engagement and outreach. Investments in trusting and sustained partnerships between an academic institution and faith communities demonstrated efficacy in increasing opportunities for providing service, access to research, and health education opportunities to communities that are typically underrepresented in research.